Plural comitative constructions in Polish - Trawinski, Beata (Proceedings of the 12th International Conference on Head-Driven Phrase Structure Grammar, 2005)
This paper provides a treatment of Polish Plural Comitative Constructionsin the paradigm of HPSG in the tradition of Pollard and Sag (1994).Plural Comitative Constructions (PCCs) have previously been treated in terms of coordination, complementation and adjunction. The objective of this paper is to show that PCCs are neither instances of typical coordinate structures nor of typical complement or adjunct structures. It thus appears difficult to properly describe them by means of thestandard principles of syntax and semantics. The analysis proposed in this paper accounts for thesyntactic and semantic properties of PCCs in Polish by assuming an adjunction-based syntactic structure for PCCs, and by treating the indexical information provided by PCCs not as subject toany inheritance or composition, but as a result of applying a set of principles on number, gender andperson resolution that also hold for ordinary coordinate structures.